KONTRADIKSI PENERAPAN NINE DASH LINE DENGAN FREEDOM OF NAVIGATION DAN DAMPAK GEOPOLITIK DI ASEAN - Rousseau Jordan Angelo Napitu, (2022)
This paper aims to convey to the reader the Contradictions of the Implementation of the Nine Dash Line with Freedom of Navigation and the Impact of Geopolitics in ASEAN. The type of research used in the preparation of this paper is a juridical- normative approach, namely the type of approach using the provisions of the legislation in force in a country or a doctrinal legal approach method. The benefits of this research are expected to be used to increase knowledge and knowledge in the field of law, especially international law and increase knowledge and studies on the concept of bilateral, multilateral, and also political approaches in resolving disputes between countries. Furthermore, it is hoped that this research can make a positive contribution as reference material and reference for future research. The results of this study indicate that the rules of international law have not been able to fully accommodate the disputes that occur, especially in the case of the South China Sea dispute where when there has been a decision made by the Permanent Court of Arbitration (PCA), but it is not implemented properly by China. . There is no enforcement or coercion that can be done by the Permanent Court of Arbitration (PCA) to pressure the People's Republic of China (PRC). However, one thing that can at least be used to resolve the China maritime dispute is the geopolitical concept. Geopolitics, of course, will always go hand in hand with the application of international law. The geopolitical aspect will be very helpful for policy makers to help resolve disputes because in general geopolitics is a method of foreign policy analysis to be able to explain and even predict what policies will happen in the future in politics, law based on geography.